CHALLENGES FOR TEACHERS OF ENGLISH FOR SPECIFIC PURPOSES IN HIGHER EDUCATION - Марія Кокор (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The paper dwells on the problems related to teaching English for Specific Purposes (ESP) in higher educational establishments and a range of currently existing issues in higher education in Ukraine. On the basis of theoretical research and empirical findings the key aspects of ESP teaching have been analyzed, in particular, the relevance of leaners' needs analysis for designing a syllabus and the need for enhanced collaboration of ESP teachers with experts in specific fields have been emphasized, the necessity of reflective thinking in daily professional practice and a shift to reflective learning activities in the preparation of future teachers of foreign languages have been singled out  as well as discussed. A few possible solutions have been theoretically justified, one of which is the necessity of introducing teacher ESP training programs into the curriculum of foreign teacher preparation programs.